Placenta Senescence and the Genesis of Preeclampsia: Is There Any Potential Role? – A Review - Nugraha, Azka Ardian; Nugrahani, Annisa Dewi; Adriansyah, Putri Nadhira Adinda; Shodiq, Ja’far; Santoso, Dhanny Primantara Johari (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2024)
Introduction: Preeclampsia is a hypertensive disorder of pregnancy and is responsible for around 800 maternal deaths. The etiologies of preeclampsia remain unidentified, although the premature senescence of the placenta is a possible cause. To date, various markers such as oxidative stress and mitochondrial dysfunction have been identified to be related to placental aging.Method: This study uses a narrative review approach; the search engines used are Scopus, PubMed, and Cochrane. The keyword combinations are placenta senescence AND aging AND preeclampsia, while excluding the results that are correspondence or not written in English.Results: The senescence of the placenta has a role in the pathophysiology of preeclampsia. The epigenetic alterations marked by the changes in the trophoblast’s telomere length as the result of the damage done by ROS to the mitochondria marked by various biomarkers can lead to accelerated cell death.Conclusion: Preeclampsia is due to premature placental aging and apoptosis, resulting in widespread blood vessel lining dysfunction.Penuaan Plasenta dan Asal Mula Preeklampsia: Adakah Peran Potensial? – Sebuah TinjauanAbstrakPendahuluan: Preeklampsia adalah gangguan hipertensi pada kehamilan yang menyebabkan sekitar 800 kematian ibu. Penyebab preeklampsia masih belum diketahui, namun penuaan dini plasenta merupakan salah satu penyebabnya. Sampai saat ini, berbagai markah seperti stress oksidatif dan disfungsi mitokondria telah teridentifikasi berhubungan dengan penuaan plasenta.Metode: Penelitian ini menggunakan pendekatan tinjauan naratif dan mesin pencari yang digunakan adalah Scopus, PubMed, dan Cochrane. Kombinasi kata kunci yang digunakan adalah penuaan plasenta DAN penuaan DAN preeklampsia dan mengecualikan hasil yang bersifat korespondensi atau tidak ditulis dalam bahasa Inggris.Hasil: Penuaan plasenta memiliki peran dalam patofisiologi preeklampsia. ROS merusak mitokondria dengan mengubah panjang telomer trofoblas. Perubahan tersebut dapat menyebabkan percepatan kematian sel yang bisa ditandai dengan berbagai biomarkerKesimpulan: Preeklampsia disebabkan oleh penuaan plasenta dini dan apoptosis yang mengakibatkan disfungsi lapisan pembuluh darah yang meluas.Kata kunci: Perubahan Epigenetik, Stres Oksidatif, Penuaan Plasenta, Preeklampsia